Inventory Management of Educational Facilities and Infrastructure - Afiful Ikhwan; Fina Kholij Zukhrufin; Syamsul Arifin; Muhammad Muhson; Anisah Triyuliasari (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This research describes the inventory management of educational facilities and infrastructure at Muhammadiyah Elementary School Ponorogo. This research uses descriptive qualitative research methods. This study used data collection with observation techniques at school and interviews with the teachers concerned. The results of the study prove that the process of managing facilities and infrastructure by the standards at Muhammadiyah Elementary School Ponorogo the process consists of planning with a joint meeting to analyze the needs as a whole, procurement from the School Operational Assistance budget, grants, Muhammadiyah Association foundation funds and school cash, inventory is recorded by officers, distribution and maintenance are carried out together, for deletion is done through sorting goods, supervision and accountability by making reports. Good inventory management of infrastructure facilities will impact schools, including students getting optimal learning; teachers can utilize infrastructure facilities to attract the attention of bored students, improve school quality with good administration, and attract public attention and interest in schools.